A Network-Based Model for Mitigating Traffic Jams in Road Networks - Salih Hasan, Ahmed (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Abstract. In recent years, the city of Mosul, which is the capital city of Nineveh province in the North of Iraq, had witnessed an unstable situation (e.g., wars, internal conflicts) that led to destructing most of the infrastructure including city roads. In addition, the population of Mosul is currently concentrated on the east coast of the city. Therefore, this situation has caused a server traffic jam and the roads have become overloaded, which is time-wasting when accessing a particular place in the city. In this analytical study, the roads of the east coast of Mosul city are modeled in the form of a Road Network. The proposed approach is based on concepts inspired from Complex Networks and their measurements such as clustering coefficient, betweenness, degree, and closeness. The dataset of this work was collected from Google Earth with the support of governmental offices and road-experienced individuals. The created network represents the road network of Mosul city. In the results, suggestions and recommendations are provided, which can contribute to alleviating the problem of traffic congestion in the city of Mosul. The provided suggestions do not need a high cost because the proposed approach benefits the current road networks with few modifications. The proposed approach is applicable to any city of interest.